Diabetes mellitus among young adults in Sri Lanka- role of GAD antibodies in classification and treatment: The Sri Lanka Young Diabetes study - Katulanda, P.; Shine, B.; Katulanda, G.W.; Silva, A.; Asfir, E. L.; Sheriff, R.; Somasundaram, N.; Long, A. E.; Bingley, P. J.; McCarthy, M. I.; Clark, A.; Matthews, D. R. (Springer Nature, 2008)
Aims/hypothesis Diabetes mellitus is increasing among young adult South Asians. The aim of this study was to determine the prevalence and phenotypic characteristics of diabetes subtypes based on GAD65 autoantibody (GADA) status in those with young adult-onset diabetes in Sri Lanka. Methods Clinical, metabolic and GADA data were available for 992 consecutively recruited individuals with diabetes aged ≤45 years (age at diagnosis 16–40 years).
Diabetologia: 2008; 51; 1368-1374p.
Keywords: Autoimmune; GAD65 autoantibodies; Insulin; LADA; South Asian; Sri Lankans; Type 1 diabetes; Type 2 diabetes; Young adults